Cordelia [videorecording (DVD)] - Shergold, Adrian; Campbell-Hughes, Antonia, 1982-; Campbell-Hughes, Antonia, 1982-; Flynn, Johnny; Gambon, Michael; Fry, Joel (Screen Media, 2022)
Cordelia, a young woman living in London, meets her mysterious and alluring neighbor Frank for the first time but quickly becomes suspicious of his motives. With her twin sister away for the weekend, Cordelia is left alone and overcome with paranoia. She begins to unravel and sink back into past traumas the more that Frank tries to charm his way into her life, becoming a danger to herself and others.